Developments and Trends in Indonesian Tourism Technology Using Bibliometric Analysis - Ayulya, Agisti Mutiara; Syaifullah, Syaifullah; Hamzah, Muhammad Lutfi; Ahsyar, Tengku Khairil; Saputra, Eki (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2024)
Information technology has changed society, services, and the tourism sector has attracted many research and publications. Even though previous research aims to show an understanding of tourism technology factors, there is still little to discuss the technology factors of Indonesian tourism. Discussing scientific publications about tourism technology in Indonesia can provide a deeper understanding of the development of information technology in the Indonesian tourism sector by providing solutions. This research aims to analyze developments and trends in tourism technology factors in Indonesia from 2014 to 2023 with bibliometric analysis from R Studio and using 113 Scopus indexed articles. The methodology includes planning, keyword identification, Scopus data searches, bibliometrics, developments and trends in Indonesian tourism technology. The results of this research show an increase in publications from year to year, in annual citations there are fluctuations, the number of articles published varies with the position of Sustainability (Switzerland) being ranked first with 25 published articles, Indonesia is the country that publishes the most articles and the frequency has increasing, Indonesia has also become a top keyword, and in tourism technology trends there are two clusters within the basic themes, namely tourism and West Java, which are the direction for further research